(untitled) (Религиски дијалог и соработка, 2020)
The paper is based on the research of interethnic relations in BH society, cold interethnic relations caused by ethnic distance. Bosnia and Herzegovina, as a union of differences, a country where three majority, or constitutive, nations merge and interact is a suitable ground for emergence of social distance based on the negative ethnic and national characteristics and attitudes which are ascribed to other peoples and which develop due to negative opinion and antipathy towards other ethnic groups. The analysis includes members of three constitutive peoples, Serbs, Croats and Bosniaks, three different ethnic groups that share a common country and territory, but have different cultural heritage. The primary aim of the study was to show ethnic distance based on the level of kinship that the members of one ethnic group is ready to achieve with the members of other ethnic groups, multiethnic relations within this society, as well as the influence of ethnic and national prejudices on social distance or closeness. Today, stable ethnic relations are an important factor of stability and security in many countries and societies. Just like every ethnic group endeavors to achieve its individual and collective rights, especially minority groups, so the countries try to achieve stable interethnic relations within, as well as utmost security and stability. The countries from this region burdened with tumultuous past and ethnic conflicts are trying to achieve the greatest stability and security possible which is the reason they pay a special attention to the question of regulating their ethnic relations.